PENERAPAN PROGRAM PENDAMPINGAN UMKM DALAM MENINGKATKAN KUALITAS UMKM DI SENTRA WISATA KULINER PEGIRIAN SURABAYA - Krisnawati, Anggi; Muslimin, Muslimin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This article aims to find out the implementation and impact of the implementation of the mentoring program on improving the quality of MSMEs at the Pegirian Culinary Tourism Center. Research Methods used in this study uses a descriptive qualitative method. The data collection method includes in-depth interviews with MSME owners at the Pegirian Culinary Tourism Center who meet the research criteria as research subjects and SWK companions, observations, and documentation. Data analysis was carried out by comparing the changes that occurred before and after the implementation of the program through interviews to find out the impact of the implementation of this MSME mentoring program. The results of the study show that the mentoring program has a positive impact on MSME actors as well as in improving the quality of MSMEs at the Pegirian Culinary Tourism Center. The MSMEs involved have experienced improvements in their managerial capabilities, improved operational efficiency, and are able to access a wider market. However, challenges such as limited resources and coordination between stakeholders affect the success of the program.